Dismissal Laws in Australia: Reforms and Enforcement by Labour Courts - Benoit Pierre Freyens; Xiaodong Gong (Institute for the Study of Labor (IZA), 2015)
The paper analyses the arbitration of dismissal disputes by Australian labour courts over a 15 years' time span characterized by two major legal reforms to unfair dismissal statutes. We isolate two channels by which we think the social values of the Federal government affected the decisions of the courts: (i) through changes to established rules (the legal standards guiding decisions) and (ii) through labour court appointments (changing the composition of decision-makers). We study these two questions by analysing the probability of plaintiffs' victory in Australian labour court, using a panel of 81 judges and 2,223 decisions. We test for and subsequently exploit the randomized matching of labour court judges with unfair dismissal cases. We also test for and address the Priest-Klein selection effect, which is known to potentially invalidate analysis of trial cases. Using several model specifications we find significant effects from both channels: statutory reforms and judges' work background have strong and significant effects on case outcomes.
Keywords: J52; K31; K41; 330; unfair dismissal laws; judicial backgrounds; case outcomes